UPAYA DIVERSI TERHADAP ANAK YANG MELAKUKAN TINDAK PIDANA DALAM PERSPEKTIF KEADILAN RESTORATIF - Kelibia, Muhammad Umar (IBLAM LAW REVIEW, 2023)
The condition of handling children who commit crimes is very apprehensive. Many children facing criminal cases must be detained in a place that is disproportionate to the capacity of the existing Children's Penitentiary (Lapas). Often law enforcement officials make peace so that cases are not forwarded to the legal process. But peace like this is not the expected diversion mechanism, because peace here does not pay attention to the best interests of the child. This is understandable, considering that in carrying out diversion as desired, law enforcement officials do not yet have a legal umbrella, besides that there are no implementation guidelines or technical instructions. for law enforcement officials to implement ways of solving diversion for children who are facing criminal cases. This type of legal research is normative legal research. The nature of the research in this study is analytical descriptive in nature. The type of data used in this research is library research. By using the concept of restorative justice, the expected result is a reduction in the number of children who are arrested, detained and sentenced to prison; eliminating the stigma/stamp and returning children to normal human beings so that it is hoped that they will be useful in the future, juvenile offenders can realize their mistakes, so they do not repeat their actions reducing the workload of the police, prosecutors, detention centers, courts and prisons; saving state finances, not causing a feeling of revenge because the perpetrator has been forgiven by the victim, quickly getting compensation; empowering parents and the community in overcoming child delinquency and reintegrating children into society. Especially Indonesia, which has made Law no. 11 of 2012 concerning the Juvenile Criminal Justice System which has regulated the concept of diversion and restorative justice